2021
DOI: 10.1021/acsomega.1c05386
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study into Lanthanide Speciation in Deep Eutectic Solvents

Abstract: Deep eutectic solvents are a new class of green solvents that are being explored as an alternative for used nuclear fuel and critical material recycling. However, there is a paucity of knowledge regarding metal behavior in them. This paper explores the underlying chemistry of rare-earth elements in choline chloride-based deep eutectic solvents by using a multi-technique spectroscopic methodology. Results show that speciation is highly dependent on the choice of the hydrogen-bond donor. Collected EXAFS data sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…These results will be discussed in the context of previous reports of anomalous reaction conditions (i.e., low temperatures) required to form high-activity nanostructures via DES solvothermal reactions . We will explore the hypothesis that this is due to unusual coordination complexes formed about rare earth centers in these mixtures. , Herein, we show that direct experimental neutron scattering measurements can connect local Ce 3+ ion speciation with bulk structure by giving insights into the impact of ion complexes on mean liquid structuring and interspecies interactions as a function of the DES water content.…”
Section: Introductionmentioning
confidence: 75%
“…These results will be discussed in the context of previous reports of anomalous reaction conditions (i.e., low temperatures) required to form high-activity nanostructures via DES solvothermal reactions . We will explore the hypothesis that this is due to unusual coordination complexes formed about rare earth centers in these mixtures. , Herein, we show that direct experimental neutron scattering measurements can connect local Ce 3+ ion speciation with bulk structure by giving insights into the impact of ion complexes on mean liquid structuring and interspecies interactions as a function of the DES water content.…”
Section: Introductionmentioning
confidence: 75%
“…For instance, the removal of chloride from the system will change the ligand of Nd from chloride to acetate or lactate, which could lead to more stable and hence soluble species. 35 It has been found that the solvent nature affects the formation of metal complexes, resulting in different coordination numbers and ligands. [35][36][37][38] For instance, Amphlett et al 35 recently reported the effect of HBDs (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…35 It has been found that the solvent nature affects the formation of metal complexes, resulting in different coordination numbers and ligands. [35][36][37][38] For instance, Amphlett et al 35 recently reported the effect of HBDs (e.g. ethylene glycol, urea, and lactic acid) in choline chloride-based DESs on the coordination environment of lanthanides (Ln), including Nd, using different spectroscopic techniques.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative source of different electrochemical behaviour involves the type of HBD present in a DES system, as these can change the physical and chemical properties of the solvent, as well as being able to act as complexing agents. 8,11,12,58 UV-vis spectra of copper chloride in a selection of DESs containing HBDs with different pK a values show that copper speciation is generally unaffected by the choice of HBD, except in the cases of the oxalic acid system where the precipitation of copper oxalates took place above 0.01 mol dm À3 , and in the urea system where ammonia formation results in the formation of blue copper-ammonia complexes. Images of these solutions are shown in Fig.…”
Section: Effect Of Hydrogen Bond Donormentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The speciation, and hence reactivity, of these metal complexes is generally determined by the anionic component of the IL or DES, 8 except when significantly stronger ligands such as cyanide are already present on the starting metal salt, 9 or when the metal ion has an oxophilic character. 10,11 In certain cases when the hydrogen bond donor (HBD) component of the DES is strongly coordinating, this can result in metal complexes being precipitated, such as nickel ions in the presence of oxalate, or lead ions in the presence of lactate. 12 The use of ILs or DESs containing anions with greater coordination strength often results in metal complexes with higher stability constants, hence greater electrodeposition overpotentials are often required to electrowin metals from such solutions.…”
Section: Introductionmentioning
confidence: 99%